Perbedaan Return Saham Sebelum dan Sesudah Stock Split Pada Perusahaan Indeks LQ-45 di BEI Periode 2019-2023 - Raya, Diki Kurnia; Widuri, Trisnia; Nadhiroh, Umi (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to determine whether there is a significant difference in stock returns before and after stock splits among companies listed in the LQ-45 Index on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A stock split is a corporate action believed to provide a positive signal to investors. This research uses a quantitative approach with an event study method. The sample consists of 14 companies that carried out stock splits while being listed in the LQ-45 Index. Stock returns are calculated using an 11-day event window and a 60-day estimation period. The data analysis technique employed is the paired sample t-test to examine the difference in returns. The results show a significant difference, with a p-value of 0.006 < 0.05. However, the difference is negative, as most companies experienced a decline in stock returns after the stock split. This decrease may be caused by investors engaging in profit-taking after the stock split euphoria, or due to the short observation period, which may not have fully captured the market’s response. The author recommends that companies carefully consider the timing and implications of stock splits and ensure transparent communication with investors.